2021
DOI: 10.48550/arxiv.2102.10220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Making an $H$-Free Graph $k$-Colorable

Abstract: We study the following question: how few edges can we delete from any H-free graph on n vertices in order to make the resulting graph k-colorable? It turns out that various classical problems in extremal graph theory are special cases of this question. For H any fixed odd cycle, we determine the answer up to a constant factor when n is sufficiently large. We also prove an upper bound when H is a fixed clique that we conjecture is tight up to a constant factor, and prove upper bounds for more general families o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This yields, for every fixed odd r, C r -free (n, d, λ)-graphs with d = Θ(n 2/r ) and λ = O( √ d). By (1.4), these graphs have surplus at most O(λn) = O((nd) (r+1)/(r+2) ), which shows that (1.3) would be optimal for all odd r. Regarding this problem, Zeng and Hou [23] showed that sp(m, C r ) ≥ m (r+1)/(r+3)+o (1) for all odd r, and very recently Fox, Himwich and Mani [14] improved the surplus to Ω r (m (r+5)/(r+7) ). We settle this problem completely by proving the following tight result.…”
Section: Cycles Of Odd Lengthmentioning
confidence: 96%
See 1 more Smart Citation
“…This yields, for every fixed odd r, C r -free (n, d, λ)-graphs with d = Θ(n 2/r ) and λ = O( √ d). By (1.4), these graphs have surplus at most O(λn) = O((nd) (r+1)/(r+2) ), which shows that (1.3) would be optimal for all odd r. Regarding this problem, Zeng and Hou [23] showed that sp(m, C r ) ≥ m (r+1)/(r+3)+o (1) for all odd r, and very recently Fox, Himwich and Mani [14] improved the surplus to Ω r (m (r+5)/(r+7) ). We settle this problem completely by proving the following tight result.…”
Section: Cycles Of Odd Lengthmentioning
confidence: 96%
“…The study of MaxCut in H-free graphs was initiated by Erdős and Lovász (see [12]) in the 70s, and has received significant attention since then (e.g. [2,3,5,6,14,20,21,23]). For a graph H, define sp(m, H) as the minimum surplus sp(G) = mc(G) − m/2 over all H-free graphs G with m edges.…”
Section: Introductionmentioning
confidence: 99%